DEVIANT BEHAVIOR IN YOUTH: METHODS OF SOCIO–PEDAGOGICAL PREVENTION - Bokhanova, A.S.; Zhaparova, L.B. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This article analyzes the causes of deviant behavior in children, explores the concept of «deviance,» and its role in modern pedagogy. It examines the interaction of children with deviant behavior with social educators, parents, and self–knowledge teachers. Special attention is given to measures for the prevention and correction of behavioral deviations.
Keywords: deviance; problem child; social maladjustment; psychological and pedagogical assistance; educational rehabilitation